ORGANIZATIONAL, ECONOMIC AND LEGAL PRINCIPLES OF EFFECTIVE USE OF LAND BY ENTERPRISES IN UKRAINE (INNOVATIVE ECONOMY, 2022)
Parkhomets M.K., Uniiat L.M., Chorna N.P., Kostetskyi Ya.I. ORGANIZATIONAL, ECONOMIC AND LEGAL PRINCIPLES OF EFFECTIVE USE OF LAND BY ENTERPRISES IN UKRAINEPurpose. The aim of the article is the in-depth study of organizational, economic and legal principles of effective land use by Ukrainian enterprises.Methodology of research. The methodological basis of the study is the dialectical method of scientific knowledge. In the course of the research general scientific and special methods were used, in particular analysis and synthesis (for the analysis of the dynamics of fertilizer application and the level of crop yield); grouping of enterprises by area of agricultural land (for the analysis of economic efficiency of production); economic and statistical (to assess the lease and sale of land); abstract and logical (to outline the main directions of organizational, economic and legal principles of effective use of agricultural land in Ukraine, the formation of conclusions and proposals to improve state monitoring, regulation and support of enterprises).Findings. It is investigated that the yield and efficiency of crop production largely depend on the level of technical and technological innovation and resource-saving tools, which helps to perform work on time and reduce losses. There is a direct relationship between the level of yield and efficiency of production of all crops and the application of organic and mineral fertilizers. Unfortunately, the share of fertilized sown areas on average in 2016-2019 in Ukraine was: mineral fertilizers – 89.5%, and organic - only 3.5%. There is a tendency to increase the number of enterprises in the area of land, which indicates a positive direction of concentration and efficiency of production.It was found that the efficiency of crop and livestock production by Ukrainian enterprises has been quite unstable in recent years and is declining due to a significant increase in energy prices and rising production costs. It is established that an important area of increasing the area of land and improving their use is the lease and sale of agricultural land. At the same time, the Ukrainian land market has been operating under a moratorium for the last 15-18 years, creating a wide field of action for corruption and leading to a loss of UAH 56 billion in GDP.It is investigated that an important direction of improving the efficiency of land use and increasing jobs in the country is to restore the work of domestic plants for the production of resource-saving technical and technological means (tractors, seeders, combines, etc.). It was found that a powerful way to increase land use is to strengthen state monitoring and control over the development of agro-industrial production in order to anticipate possible price disparities in some foods and their regulation.Originality. The substantiation of the influence of organizational-economic and legal bases on the economic efficiency of agricultural lands use by Ukrainian enterprises was further developed.Practical value. Substantiated research results can be used by agricultural enterprises, factories for the production of agricultural machinery (combines, machines, tractors, etc.) and the Ukrainian authorities to improve the economic efficiency of agricultural land use.Key words: land; resource-saving equipment; mineral and organic fertilizers; crop yields; rent and sale of land plots; land use efficiency.
Keywords: land; resource-saving equipment; mineral and organic fertilizers; crop yields; rent and sale of land plots; land use efficiency.